TOKSISITAS EKSTRAK DAUN Lantana camara L. TERHADAP HAMA Plutella xylostella L. - Hendrival Hendrival; Khaidir Khaidir (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2012)
Toxicity n-hexane leaf extract Lantana camara and its active fractions were evaluated for their insecticidal activit ies against Plutella xylostella larvae. The method included sample extraction, fractionation, and toxicity examination of leaf extract L. camara and its active fractions against P. xylostella larvae. The extracts were applied by residue method. Fractionation of active compounds from extract n-hexane was conducted by a vacuum liquid chromatography by using a stationary phase of silicate gel GF254 and mobile phase of n-hexane, etil acetate, and methanol which produced five fractions, that is fractions A, B, C, D, and E. Leaf extract of L. camara and its fractions possessed an insecticidal activity causing mortality to P. xylostella larvae. The results showed that LC50 of crude extract at 3 and 4 day after applications was 0,936 and 0,651%, while LC50 of fractions A = 0,386 and 0,178%; fractions C = 0,327 and 0,132; fractions D = 0,617 and 0,318%; fractions E = 0,622 and 0,244%.